2016
DOI: 10.1093/ofid/ofw212
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic Value of Transient Elastography in Human Immunodeficiency Virus-Infected Patients With Chronic Hepatitis C

Abstract: Background.Our objective was to study the prognostic value of liver stiffness (LS) in HIV-infected patients with chronic hepatitis C (CHC).Methods.We analyzed HIV-infected patients with compensated CHC and at least 1 determination of LS. The primary outcome was the occurrence of liver-related events (LRE), namely, decompensation or hepatocellular carcinoma, whichever occurred first. We selected patients without sustained viral response (SVR) or end-of-treatment response (ETR) during follow-up and allocated the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0
1

Year Published

2017
2017
2019
2019

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 41 publications
1
10
0
1
Order By: Relevance
“…The pressure reading on TE in kilopascals (kPa) was used to define the degree of hepatic fibrosis including cirrhosis. In keeping with Australian guidelines [4], in mono-infected patients the kPa cut-off for cirrhosis was >12.5kPa, while patients with HIV or HBV co-infection were considered to have cirrhosis with kPa values of >12.0kPa [13, 2829]. TE was undertaken by practitioners trained in its use.…”
Section: Methodsmentioning
confidence: 99%
“…The pressure reading on TE in kilopascals (kPa) was used to define the degree of hepatic fibrosis including cirrhosis. In keeping with Australian guidelines [4], in mono-infected patients the kPa cut-off for cirrhosis was >12.5kPa, while patients with HIV or HBV co-infection were considered to have cirrhosis with kPa values of >12.0kPa [13, 2829]. TE was undertaken by practitioners trained in its use.…”
Section: Methodsmentioning
confidence: 99%
“…Coinfection increases liver damage and fibrosis. Pérez-Latorre et al [19] reported elevated liver stiffness in coinfected patients. They also concluded that stiffness values above 12 kPa can be used to determine liver fibrosis.…”
Section: Discussionmentioning
confidence: 98%
“…A systematic review and meta-analysis in HIV/HCV co-infected persons, encompassing 6 studies, concluded TE had similar pooled sensitivity and specificity for prediction of liver-related events as in HCV mono-infection, with better performance in cirrhotics than those with intermediate stages of fibrosis, and with no impact of CD4 count on diagnostic accuracy [53]. A retrospective study of 957 HIV/HCV co-infected patients with compensated cirrhosis found that liver stiffness <12 kPa, measured by TE, had excellent negative predictive value for liver related events after a median follow up of 6 years, with a proportional increase in events for pressures above this cutoff [54]. In a cohort of 275 HIV/HCV co-infected patients with cirrhosis, a significant increase in liver stiffness measured by TE over a median follow-up time of 32 months was associated with a higher risk of hepatic decompensation and HCC [55].…”
Section: Staging Liver Diseasementioning
confidence: 99%